Experimental study of unsaturated-saturated permeability characteristics of slip zone soil in deposits - LI Yue; XU Wei-ya; YI Kui; XIE Wei-chau; ZHANG Qiang; MENG Qing-xiang (Rock and Soil Mechanics, 2021)
There are many landslide deposits in the reservoir and bank areas of hydropower projects in southwest China. These deposits are easy to deform and fail along the existing sliding zone under hydrodynamic conditions, such as rainfall and reservoir water fluctuation. The slip soil in Dahua landslide deposits which are located at the Dahuaqiao Hydropower Plant in the Lancang river basin of southwest China, was studied as an example. The experimental study was carried out to explore the soil-water characteristic curve (SWCC) of slip soil. The permeability characteristics and the evolution in the unsaturated seepage process were analyzed, and the saturated permeability characteristics under different confining pressures and osmotic pressures were studied. The results indicated that the VG model could be used to describe the SWCC and the variation of relative permeability coefficient of Dahua slip zone soil. Through the saturated permeability test, it is found that under the same other conditions, the larger the confining pressure is, the weaker the saturated permeability of the slip soil is; while the larger the osmotic pressure is, the stronger the saturated permeability is. Furthermore, the saturated permeability characteristics of the slip zone soil manifested a strong non-Darcy flow behavior, and the relationship between permeability velocity and hydraulic gradient satisfied the Forchheimer binomial model. When the confining pressure was low, the linear term coefficient of velocity had a more significant effect on the permeability, whereas the quadratic term coefficient of velocity gradually dominated in the seepage process with the increase of confining pressure.